INTEGRASI NILAI-NILAI ISLAM DALAM PENDIDIKAN LINGKUNGAN DAN EKOLOGI - M.Fadhillah; Asep Rahmatullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The global environmental crisis—marked by climate change, deforestation, pollution, and the degradation of ecosystems—demonstrates that ecological issues are caused not only by technical factors, but also by a moral crisis and a lack of human awareness in interacting with nature. On the other hand, environmental education across various educational institutions remains predominantly focused on mastering scientific knowledge, rendering it insufficiently capable of shaping students' sustainable ecological behavior. This study aims to analyze the integration of Islamic values into environmental education and ecology to foster a holistic ecological awareness through theological and pedagogical approaches. This study employs a qualitative library research methodology. Data were gathered from the Qur'an, Hadith, Islamic education literature, as well as academic articles on environmental education, Islamic eco-theology, and curriculum integration. The data were analyzed using content analysis techniques through data reduction, categorization, interpretation, and synthesis of relevant concepts. The findings indicate that the integration of environmental education based on Islamic values can be developed through four fundamental values: khalifah (stewardship) as the foundation of responsibility for environmental management, amanah (trust) as the principle of conserving natural resources, mizan (balance) as the basis for maintaining ecosystem equilibrium, and ihsan (excellence/benevolence) as the orientation for cultivating responsible ecological behavior. These four values are implemented through subject-matter integration in Natural Science and Islamic Religious Education, contextual learning approaches, and the habituation of green akhlaq (eco-friendly character) within the school culture. This study concludes that integrating Islamic values into environmental education strengthens students' spiritual, moral, and ecological dimensions. Consequently, environmental education not only enhances knowledge, but also fosters ecological awareness and environmental conservation behaviors as an integral part of religious responsibility. Keywords: Islamic values integration; environmental education; ecology; eco-theology; ecological awareness.